2004
DOI: 10.1177/154405910408300802
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Regeneration by Dental Pulp Stem Cell Therapy with Recombinant Human Bone Morphogenetic Protein 2

Abstract: Regenerative medicine is based on stem cells, signals, and scaffolds. Dental pulp tissue has the potential to regenerate dentin in response to noxious stimuli, such as caries. The progenitor/stem cells are responsible for this regeneration. Thus, stem cell therapy has considerable promise in dentin regeneration. Culture of porcine pulp cells, as a three-dimensional pellet, promoted odontoblast differentiation compared with monolayers. The expression of dentin sialophosphoprotein (Dspp) and enamelysin/matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
2
28

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(284 citation statements)
references
References 28 publications
8
246
2
28
Order By: Relevance
“…Other factors, such as Msx2, Twist1, and Yy1, act as negative regulators, and the positive and negative factors work together to determine the transcriptional level of the Dspp expression. As previous studies strongly indicated that Dspp played a critical role in dentinogenesis and dentin mineralization (4 -6), the up-regulation of Dspp expression would be quite important in secondary dentin formation after exposure of odontoblast processes by dental cavity preparation (17). In this context, we can suggest that a direct application of BMP2 or activators of its downstream transcription factors in dental cavities would be a possibility to enhance secondary dentin bridge formation through up-regulation of Dspp expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other factors, such as Msx2, Twist1, and Yy1, act as negative regulators, and the positive and negative factors work together to determine the transcriptional level of the Dspp expression. As previous studies strongly indicated that Dspp played a critical role in dentinogenesis and dentin mineralization (4 -6), the up-regulation of Dspp expression would be quite important in secondary dentin formation after exposure of odontoblast processes by dental cavity preparation (17). In this context, we can suggest that a direct application of BMP2 or activators of its downstream transcription factors in dental cavities would be a possibility to enhance secondary dentin bridge formation through up-regulation of Dspp expression.…”
Section: Discussionmentioning
confidence: 92%
“…Bmp-2 is expressed in the bell stage during which dentin mineralization progresses very actively, and Dspp expression becomes detectable from the subsequent secretory stage, just following Bmp-2 expression. Previously, Nakashima (18) reported that the expression of BMP-2 is increased during terminal differentiation of odontoblast, and Iohara et al (17) indicated that BMP-2 induces Dspp mRNA expression. Chen et al (19) also proved that Dspp mRNA expression is followed by additional Bmp2 expression, through an in situ hybridization experiment.…”
Section: Dentin Sialophosphoprotein (Dspp)mentioning
confidence: 99%
“…This clearly indicates that the activity of ST on DPSC was not impaired by the micelle formation. On the other hand, accelerated DPSC differentiation into odontoblasts was observed after stimulation with BMP for more than 10 days 10) . When the ST Mi/GH that were degraded for 7 days were applied to DPSC, no in vitro odontoblastic differentiation was observed (data not shown), which suggests that it may be necessary to allow a controlled ST release to occur for more than 10 days.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that simvastatin (ST) has the potential to induce osteoblastic bone formation or enhance the expression of bone morphogenetic protein (BMP)-2 for several osteogenic cells [6][7][8] . Some investigators have demonstrated that DPSC can be differentiated into odontoblasts by BMP-2, resulting in the promotion of dentin formation [9][10][11] . On the other hand, the release of ST from gelatin hydrogel has been shown to enhance BMP-2 production from the surrounding cells, resulting in BMP-2 induced bone regeneration 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell activity has been found to be critically involved in both pre-and post-natal tooth development [59][60][61][62] and dental stabilisation in the periodontal ligament, 63,64 involved in endothelial processes in tooth development, 65 and very involved in the immunological surveillance and counteraction of the intense infective stimulus of the oral fl ora in the gingival sulcus. 66 A serious hypothesis has developed that dental disorders may be associated with other systemic illnesses characterised by increased infl ammation, such as carotid atherosclerosis, 1,6 and this enjoyed currency particularly at the National Institute of Dental and Craniofacial Research (NIDCR), 58,67,68 although contrary evidence has also been described.…”
Section: Discussionmentioning
confidence: 99%